Primary Hypertension Screening in the Urban Community of Ngawi Regency - Kurniawan Erman Wicaksono; Salihati Hanifa; Ida Nurmawati; Annisa' Arifatul Hikmah; Trisakti Halimah Delimasari (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2026)
Background: The urban population experienced epidemiological changes affecting health, with hypertension being a major issue. This study identified risk factors for primary hypertension in the urban population of Ngawi Regency.Methods: It used quantitative research with a cross-sectional approach and proportional random sampling. The sample consisted of 170 respondents aged 15–59 years, selected based on inclusion and exclusion criteria. Data collection used a sphygmomanometer for blood pressure, a scale and stature meter to calculate Body Mass Index (BMI), an Food and Agriculture Organization (FAO) questionnaire for physical activity, and a Food Frequency Questionnaire for dietary patterns. Data analysis was performed using univariate and bivariate analyses using the chi-square test with a significance level of <0.05.Results: The results showed that four variables were significantly associated with the incidence of primary hypertension: age ≥45 years (p<0.001; OR=9.178), family history of hypertension (p<0.001; OR=3.218), overeating (p=0.010; OR=3.102), and BMI and obesity (p<0.001; OR=4.970). Meanwhile, gender, physical activity, alcohol consumption, and smoking habits did not show a significant association.Conclusion: It was concluded that age, family history, diet, and BMI are the main determinants of primary hypertension in the urban area of Ngawi. Preventive measures can be implemented through health education, regular blood pressure checks, adopting a low-salt diet, increasing physical activity, and weight control to reduce the incidence of hypertension in urban communities.